The Development of Pluricultural Based Presentation Teaching Materials for BIPA Students - Rina Amalia; Irma Hildayati; Ayyukum Akhsanu Amala; Dyah Ayu Sukma Wardhani; David Widyanto Putra; Prima Vidya Asteria (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
This study discusses the preparation of pluricultural-based presentation teaching materials for BIPA students. BIPA students need to master the culture in Indonesia. The Indonesian culture needs to be linked to the culture in the student's home country so that students can adapt to Indonesian culture, especially Indonesian culture which is contrary to the culture in the student's country of origin. The purpose of this research is to compile pluricultural-based presentation teaching materials for BIPA level 4 students. With the ADDIE model development method, the results of this study indicate that pluricultural-based presentation teaching materials for BIPA level 4 students are prepared by taking into account their suitability with SKL and the shortcomings of BIPA learning at State Universities. Surabaya. Pluricultural-based presentation teaching materials for BIPA level 4 students are prepared through a structured process, namely needs analysis, drafts of teaching materials are designed, and teaching materials are prepared. The limitation of this research is that this research was carried out until the stage of developing teaching materials, not yet at the stage of testing teaching materials and evaluating them. Keywords: teaching materials, pluricultural, BIPA